Effect of pore forming agent on phase transformation behavior of porous NiTi shape memory alloy - Mohd Zaki, Hafizah Hanim (Springer, 2023)
Porous NiTi shape memory alloy is of special interest for bioimplant materials due to its attractive features of NiTi dense structure such as low stiffness, high strength and excellent shape memory and pseudoelastic behavior. This porous NiTi can be produced via powder metallurgy technique using pore forming agent. The pore forming agent is used to create temporary pores that are occupied during sintering where the final sintered sample depends on the composition ratio of the pore forming agent. Porosity of up to 30–50% is predicted to be achieved which is similar to cancellous bone. However, there are queries whether the porous NiTi alloy produced may hinder the phase transformation behavior which is an indicator for shape memory behavior. Therefore, in this research, the effect of composition of pore forming agent such as calcium hydride, CaH2, on porosity level and how it correlates with phase transformation behavior of porous NiTi alloy were investigated. It shows that by increasing the percentage of CaH2 to 15 wt%, the porosity level of sintered sample can reach up to 42%. For phase transformation, there are martensitic transformation peaks observed for samples at a composition of ≤ 3wt% of CaH2 with enthalpy value of ~ 4.9 J/g. Increasing the percentage of CaH2 to ≥ 6wt%, the transformation enthalpy (ΔH) values drop significantly as the samples exhibit no martensitic transformation. This associated with the pores structure and undesirable phase that co-exist with NiTi formation, thus hindered the transformation enthalpy for porous NiTi.